Genome Editing in Neurosciences - Jaenisch, Rudolf; Zhang, Feng; Gage, Fred (Research and Perspectives in Neurosciences, 2017)
CRISPR; genetic engineering; DNA; double-strand breaks; Parkinson's disease; Huntington's disease; Rett syndrome; muscular dystrophy